Detection of Circulating Auto‐Antibodies Against Ribosylated‐LDL in Diabetes Patients. Issue 2 (26th August 2016) - Akhter, Firoz; Salman Khan, M.; Faisal, Mohammad; Alatar, Abdulrahman A.; Ahmad, Saheem
Abstract : Background: This study analyzes effect of glycation on ApoB‐100 residues by D‐ribose as D‐ribosylated‐glycated LDL might be responsible for the cause of diabetes mellitus because of its far higher antigenic ability. The binding characteristics of circulating auto‐antibodies in type 1 and type 2 diabetes patients against native and modified LDL were assessed. Methods: T1 Diabetes ( n = 43), T2 diabetes patients ( n = 100) were examined by direct binding ELISA as well as inhibition ELISA, were compared with healthy age‐matched controls ( n = 50). Results: High degree of specific binding was observed by 74.42% of T1 diabetes and 45.0% of T2 diabetes patient's sera toward glycated LDL, in comparison to its native analog. Competitive inhibition ELISA reiterates the direct binding results. Furthermore, ketoamine content, Hydroxymethylfurfural (HMF) content and carbonyl content were also estimated in patient's sera healthy subjects. The increase in total serum protein carbonyl levels in the diabetes patients was largely due to an increase in oxidative stress. The increase in ketoamine as well as HMF content inpatients sera than healthy subjects is an agreement of induced glycation reaction in patients than healthy subjects. Conclusion: D‐ribosylated‐LDL has resulted in structural perturbation causing generation of neo‐antigenic epitopes that are better antigens for antibodies in T1 and T2 diabetes patients.